The Impact of Government Expenditure, Investment, and Unemployment on Indonesia's Growth: Islamic Economic Perspective - Nurjannah Anggraini; Ridwansyah Ridwansyah; Ujang Hanief Musthofa (Universitas Darwan Ali, 2026)
This study aims to analyze the influence of government expenditure, investment, and the open unemployment rate on economic growth across 34 provinces in Indonesia during the 2020–2024 period. A quantitative approach using panel data methodology was applied, utilizing secondary data sourced from the Central Bureau of Statistics (BPS) and the Directorate General of Fiscal Balance (DJPK). Data analysis was conducted through panel data regression using EViews 9 software, with the Fixed Effect Model (FEM) selected as the best-fit model. The results indicate that, partially, government expenditure has no significant effect on economic growth. Conversely, investment has a positive and significant impact, while the open unemployment rate has a negative and significant effect on economic growth. From an Islamic economic perspective, economic growth should not be oriented solely toward increasing material output but must also encompass the creation of justice, balance, and general welfare (maslahah) for the entire society